Role of lactic acid bacteria during meat conditioning and fermentation: Peptides generated as sensorial and hygienic biomarkers - Fadda, Silvina G. (2010)
The microbial ecology of meat fermentation is a complex process in which lactic acid bacteria (LAB) and coagulase-negative cocci play a major role. The present work reviews the most significant developments in which LAB are the main characters acting both as starter cultures improving the sensorial quality and as biopreservative agents. New findings about the identification of low molecular weight peptides arisen from protein hydrolysis in dry fermented sausages and their relation with flavor is presented. Also, a brief description of a proteomic approach is detailed in order to exemplify its application as a tool in the search for improved LAB strains that will contribute to food quality and safety. Finally, the most important features of bacteriocinogenic LAB and its bacteriocins in bioprotection of meat and meat products are analyzed.